An investigation of factors influencing the acceptance of open access publishing among medical researchers in Iran / Leila Khalili - Khalili, Leila (2011)
Open access publishing provides unlimited free access to peer-reviewed articles published in open access journals. It is a way of sharing scientific knowledge and provides equal access to researchers from all over the world, especially for those unable to afford paid subscriptions. The success of this scholarly communication media depends a great deal on its acceptance by researchers. Several studies have previously investigated open access from the perspective of researchers in developed countries. However, because of diverse cultural, educational, economic and technological factors in the world, there is no ―one-size-fits-all‖ solution. It is well known that developing countries lag behind in open access practices. As a developing country, Iran has not been the subject of much research and the opinions of Iranian researchers regarding open access have not been investigated well. The aim of this study was to determine the current status of open access among Iranian medical researchers, and the factors influencing acceptance of open access publishing among them. This study used a survey design and a questionnaire as data collection instrument. The theoretical framework for the study was based on dimensions of the UTAUT model. The sample comprised 367 clinical/basic science academic staff of medical schools at public medical universities in Iran, selected using proportionate stratified sampling. The findings of study indicate that there is low familiarity with terms, initiatives and services of open access. Researchers use six open access services (open access journals, Iranian open access journals, DOAJ, BMC, PLoS and PubMed Central) more as readers than as authors. About half (47.7%) of the researchers had not submitted any manuscripts to open access journals. The researchers had low self-archiving experience (pre-print 4.4%, post-print 16.7%), but a majority of them (71%) were keen to archive if their universities were to set up an institutional repository. Based on mean scores, seven factors -- facilitating conditions, effort expectancy, performance expectancy, attitudes, concerns with author-pay, social influence, and anxiety -- influenced acceptance of open access publishing. Results of hierarchical multiple regression indicate that out of the 14 predictors of intention to use open access journals, only experience, attitude, facilitating conditions and type of university were significant. Also, results of regression show that out of 14 predictors of the use of open access journals, only intention, social influence, attitude, academic ranking, facilitating conditions, type of university and familiarity were significant key predictors. The results also suggest that researchers in top universities used open access journals more than researchers in lower ranked universities, but those from lower ranked universities had greater intentions to use these journals in future. The influence of concerns with author-pays on intention to use open access journals among researchers in Type One universities was higher than researchers in Type Two and Three universities. Also the influence of concerns with author-pays on use of open access journals among female researchers was higher than male ones. Eight constructs and six demographic factors together explain 22.3% of the variance in the use of open access journals. Seven constructs and seven demographic factors together explain 24.1% of the variance in intention to use open access journals. This study is significant in that, it provided a description of the current status of open access among Iranian medical researchers. It also investigated the acceptance of open access among researchers based on a theoretical framework derived from the UTAUT model, as well as inclusion of attitudes and anxiety as dimensions influencing acceptance.